Characterization of Silicon-Photomultipliers for a Cosmic Muon Veto detector. (22nd November 2021) - Jangra, M.; Majumder, G.; Saraf, M.; Satyanarayana, B.; Shinde, R.R.; Upadhya, S.S.; Datar, V.M.; Glenzinski, D.A.; Bross, A.; Pla-Dalmau, A.; Zutshi, V.V.; Group, R.C.; et al.
Abstract: A Cosmic Muon Veto (CMV) detector using extruded scintillators is being designed around the mini-Iron Calorimeter detector at the transit campus of the India-based Neutrino Observatory, Madurai for measuring its efficiency at shallow depth underground experiments. The scintillation signal is transmitted through a Wavelength Shifting (WLS) fibre and readout by Hamamatsu Silicon-Photomultipliers (SiPMs). A Light Emitting Diode (LED) system is included on the front-end readout for in-situ calibration of the gain of each SiPM. A characterization system was developed for the measurement of gain and choice of the overvoltage ( V ov ) of SiPMs using the LED as well as a cosmic muon telescope. The V ov is obtained by studying the noise rate, the gain of the SiPM, and the muon detection efficiency. In case of any malfunction of the LED system during the operation, the SiPM can also be calibrated with the noise data as well as using radioactive sources. This paper describes the basic characteristics of the SiPM and the comparison of the calibration results using all three methods, as well as the V ov of the SiPMs and muon selection criteria for the veto detector.